A quantitative analysis of a modified feeding method for rearing Cimex lectularius (Hemiptera: Cimicidae) in the laboratory. Issue 10 (18th March 2013) - Chin‐Heady, Eva; DeMark, Joseph J; Nolting, Steve; Bennett, Gary; Saltzmann, Kurt; Hamm, Ronda L
Abstract: BACKGROUND: A modified artificial feeding system was developed for rearing Cimex lectularius and compared with the most widely used artificial feeding method which requires custom‐made glassware and a circulating water bath to warm the blood. The petri dish method reduces some of the drawbacks from the current water bath method, such as the possibility of flooding bed bug rearing jars with water or blood and the need for expensive custom‐made glassware. RESULTS: Field and lab strain first instar nymphs were given a 15 or 30 min interval to feed for 6–9 weeks. Analysis of bed bugs that fed during a 6 week time period showed that there was no significant difference in the numbers that fed using the petri dish method compared with those that fed using the water bath method. Development of the nymphs also showed that there was no significant difference in the time required to produce adults by either method. CONCLUSION: The petri dish method is an attractive alternative to the water bath method. Set‐up is less complex, quicker, multiple jars of bed bugs can be fed at the same time, petri dishes of blood are disposable for easy clean‐up and the potential of fatality due to flooding with blood or water is reduced. © 2013 Society of Chemical Industry